INTERNALIZATION OF GEN-Q CHARACTERS IN ELEMENTARY SCHOOL THROUGH CALISA LEARNING - Bali, Muhammad Mushfi El Iq; Rozhana, Kardiana Metha (Faculty of Tarbiyah and Teacher Training, Universitas Islam Negeri Alauddin Makassar, 2022)
The purpose of this study was to determine the efforts to form students' Gen-Q, as well as the supporting and inhibiting factors in the effort to form students' Gen-Q through the CALISA program. This study used a descriptive qualitative research method with a case study approach. The method used in this study is a qualitative method that collects data using observation, interview, and documentation. The data analysis applied was a descriptive qualitative analysis of data reduction, data models, and conclusion. The results of this study are the efforts to form a Gen-Q students, including holding the Gen-Q activities in: 1) the CALISA program, 2) understanding the Quran, and 3) practicing the Qur’an. Factors supporting the CALISA program include: 1) the availability of supporting facilities and infrastructure, 2) the participation of teachers and guardians of students, 3) the level of student awareness, and 4) discipline. Whereas, the inhibiting factors are: 1) the influence of students' family conditions, 2) the influence of the community environment, and 3) the anomaly of student motivation to shape the Gen-Q students through the CALISA program at SDN Sumberanyar I Paiton Probolinggo. Abstrak: Tujuan penelitian ini adalah mengetahui upaya pembentukan Gen-Q pebelajar, serta faktor pendukung dan penghambat dalam upaya membentuk Gen-Q pebelajar melalui program CALISA. Penelitian ini menggunakan metode penelitian deskriptif kualitatif, dengan pendekatan studi kasus. Metode yang digunakan dalam penelitian ini yaitu metode kualitatif yang pengumpulan datanya menggunakan observasi, wawancara, dan dokumentasi. Analisis datanya menggunakan analisis deskriptif yaitu reduksi data, model data, dan penarikan kesimpulan. Hasil dari penelitian ini yaitu adanya upaya pembentukan Gen-Q pebelajar diantaranya mengadakan kegiatan Gen-Q dalam: 1) program CALISA, 2) memahami Alquran, 3) mengamalkan Alquran. Faktor pendukung program CALISA diantaranya: 1) tersedianya sarana dan prasarana yang mendukung, 2) partisipasi pembelajar dan wali murid, 3) tingkat kesadaran pebelajar, dan 4) tata tertib, sedangkan faktor penghambatnya yaitu: 1) adanya pengaruh kondisi keluarga pebelajar, 2) pengaruh lingkungan masyarakat, 3) anomali motivasi pebelajar dalam upaya membentuk Gen-Q pebelajar melalui program CALISA di SDN Sumberanyar I Paiton Probolinggo.